"The Group Must Come First Next Time": Students' Self-Assessment of Groupwork in a First-Year Criminal Justice Topic. Issue 1 (2nd January 2020) - Melville, Angela
Abstract: Students are increasingly conceived as active learners who collaborate in their own learning rather than being passive recipients of knowledge. This paper provides a qualitative examination of first year criminology students' engagement with two methods for encouraging students to become active and collaborative learners: a groupwork exercise and student self-assessment. Most previous research has examined teachers' views of groupwork and the use of self-assessment by students to rate their own academic performance. In contrast, this paper analyses whether self-assessment contributes to students' effective learning in a groupwork exercise. Analysis reveals that while self-assessment is valuable in producing feedback about teaching design, it is less effective in promoting student critical self-reflection and self-learning. The results also suggest several features of groupwork exercises that are necessary to promote students' deep learning.